The effect of plasma free fatty acids and long-chain triglycerides on glucose metabolism in uncomplicated falciparum malaria. - Davis, T; Supanaranond, W; Pukrittayakamee, S; Crawley, J; Villaiwanna, N; White, N (1995)
To investigate the therapeutic potential of increased plasma free fatty acid (FFA) and triglyceride concentrations in hypoglycaemic patients receiving quinine, 32 untreated Thai adults with uncomplicated falciparum malaria were allocated at random to one of 4 regimens: 2 mg/kg/min dextrose infused over 60 min either alone (group A) or with a prior injection of 5000 units of heparin and simultaneous Intralipid infusion (group C), or 4 min/kg/min dextrose alone (group B) or with heparin and Intralipid (group D). Quinine (10 mg/kg) was also infused over 60 min in all cases. In patients of groups A and C, mean changes in plasma glucose concentrations from the beginning to the end of the infusion were 0.1 (SD 0.8) and 1.0 (SD 0.7) mmol/L respectively (P = 0.015). In groups B and D, plasma glucose increased by 1.8 (SD 1.2) and 2.2 (SD 0.4) mmol/L respectively (P < 0.5). Plasma FFA levels fell by approximately 50% during the infusion in groups A and B but increased by a similar percentage in groups C and D. Despite significant mean increases in plasma insulin during the infusion (from 12.2 milliunits (mu)/L in group A to 38.8 mu/L in group D), no rebound hypoglycaemia was observed in any patient during the ensuing 7 h. These data suggest that the glycaemic response to dextrose given at high rates, which match average glucose utilization in a severely ill patient with malaria, is not augmented by increased plasma FFA and long-chain triglycerides. However, this strategy increases the glycaemic efficacy of lower dextrose infusion rates and the combination could, therefore, reduce the volumes of hypertonic dextrose required to prevent hypoglycaemia in severely ill patients in whom optimal fluid balance is crucial.